Systems methodology for software - Rus, Teodor. (World Scientific, 1993)
SYSTEM SOFTWARE AND SOFTWARE SYSTEMS: Concepts and Methodology is intended to offer a systematic treatment of the theory and practice of designing and implementing system software.The two volumes systematically develop and apply the systems methodology for software development. For that the concept of a system is analysed and various types of systems used in computer science are systematized into a concept of an ad hoc system that is suitable as a mechanism for software development. The kernel of this methodology consists of a systematic approach for ad hoc systems development (specification, implementation, validation). The hardware and the software of a computer system are specified as ad hoc systems. Examples from various architectures, languages, and operating systems are provided as illustrations. Problems and their suggested solutions are provided at the end of each chapter. Further readings and a list of references conclude each chapter.These volumes are self-contained and may be used as textbooks for an introductory course on system software and for a course on operating system. However, a broad spectrum of professionals in computer science will benefit from it.